‘Something that helped the whole picture’: Experiences of parents offered rapid prenatal exome sequencing in routine clinical care in the English National Health Service - McInnes‐Dean, H; Mellis, R; Daniel, M; Walton, H; Baple, EL; Bertoli, M; Fisher, J; Gajewska‐Knapik, K; Holder‐Espinasse, M; Lafarge, C; Leeson‐Beevers, K; McEwan, A; et al. (Wiley, 2024)
Objectives: In October 2020, rapid prenatal exome sequencing (pES) was introduced into routine National Health Service (NHS) care in England. This study aimed to explore parent experiences and their information and support needs from the perspective of parents offered pES and of health professionals involved in its delivery. Methods: In this qualitative study, semi‐structured interviews were conducted with 42 women and 6 male partners and 63 fetal medicine and genetic health professionals. Interviews were transcribed verbatim and analysed using thematic analysis. Results: Overall views about pES were positive and parents were grateful to be offered the test. Highlighted benefits of pES included the value of the additional information for pregnancy management and planning for future pregnancies. An anxious wait for results was common, often associated with the need to make decisions near to 24 weeks in pregnancy when there are legal restrictions for late termination. Descriptions of dealing with uncertainty were also common, even when results had been returned. Many parents described pES results as informing decision‐making around whether or not to terminate pregnancy. Some professionals were concerned that a non‐informative result could be overly reassuring and highlighted that careful counselling was needed to ensure parents have a good understanding of what the result means for their pregnancy. Emotional support from professionals was valued; however, some parents felt that post‐test support was lacking. Conclusion: Parents and professionals welcomed the introduction of pES. Results inform parents' decision‐making around the termination of pregnancy. When there are no diagnostic findings or uncertain findings from pES, personalised counselling that considers scans and other tests are crucial. Directing parents to reliable online sources of information and providing emotional support throughout could improve their experiences of care.